2021
DOI: 10.1186/s12887-021-02612-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth of preterm very low birth weight infants discharged with weight of less than 1500grams

Abstract: Early discharge of preterm very low birth weight (VLBW) infants is at times inevitable in low resource settings. The implication of such practice on the growth of this high-risk population is not known. We conducted a retrospective chart review to describe the growth of preterm VLBW infants discharged with a weight of less than 1500 g. Objectives To describe the growth of discharged preterm VLBW infants over the first 12 weeks. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
4
9
0
Order By: Relevance
“…Weeks of failure of adequate growth is followed by a recovery of weight-for-age, length-for-age, and head circumferences by latest 12 months of corrected age. Similar to other studies, catch-up growth was most rapid for growth of head circumference, followed by weight, while length recovery lagged behind and remained lowest for all infants and both gender ( 5 , 7 , 40 , 51 ). This trend is seen at birth already, with the head circumference for corrected age starting off with the values close to normal, while the weight for age z-scores were well below −2SD, and length-for-age below −3SD.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Weeks of failure of adequate growth is followed by a recovery of weight-for-age, length-for-age, and head circumferences by latest 12 months of corrected age. Similar to other studies, catch-up growth was most rapid for growth of head circumference, followed by weight, while length recovery lagged behind and remained lowest for all infants and both gender ( 5 , 7 , 40 , 51 ). This trend is seen at birth already, with the head circumference for corrected age starting off with the values close to normal, while the weight for age z-scores were well below −2SD, and length-for-age below −3SD.…”
Section: Discussionsupporting
confidence: 87%
“…Our study could further confirm the findings that many preterm and VLBW infants struggle to gain weight and height appropriately, especially in their first year of life ( 5 , 7 , 11 , 26 , 31 , 37 ). Weeks of failure of adequate growth is followed by a recovery of weight-for-age, length-for-age, and head circumferences by latest 12 months of corrected age.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Poor growth is related to poor neurodevelopmental outcomes; hence, the importance of comprehensive follow-up of VLBW infants is important to improve various long-term outcomes. 25 26 However, in Korea, low rates of follow-up and limitation of detailed outcomes remain challenging issues. By indirectly integrating the sporadic clinical data of VLBW obtained in the NHIS and KNN, we identified disparities in the follow-up rate and incidence of morbidities of VLBW infants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported in other series, as described by Stoll et al with preterm infants born between 2005 and 2012 [ 33 ]. A lower daily weight gain was also observed in the first 4 weeks in the first quinquennium, a parameter related to growth restriction [ 22 , 34 ]. We observed that the lower daily weight gain in the first 4 weeks was related to the risks of short stature at 2 years.…”
Section: Discussionmentioning
confidence: 99%